The Implementation of Community Participation Guidebook Development as an Effort in Environmental Preservation of Air Manis Beach in Padang City - Aini, Wirdatul; Syuraini, Syuraini (Universitas Negeri Semarang, 2023)
This article aims to describe the implementation of the development of community participation guidebook in the tourism environmental preservation which includes the testing of validity, practicality, and effectiveness of community participation guidebook in preserving the coastal tourism environment. Quantitative and qualitative research approaches with research and development design. The population of this research were community of coastal tourism, and the samples were food vendors, accessories seller, parking rangers, and tourist which determined purposively. The validity and the practicality tests were obtained from experts in educational, and tourism fields, also from the City Department of Environmental Service, and City Department of Tourism. The data collection technique used are questionnaire for the validity, practicality, and experiment test. Questionnaore were used to gather data on the process of the development of community participation guidebook. The subject of the implementation of the guidebook is the communityin the tourism area, and the experiment is to test the effectiveness of the guidebook. The research findings of the validity test of the content, educational technology, and Indonesian language are very precise, and the practicality result is very good. Test of the effectiveness of the guidebook test is to increase the community participation in preserving the coastal tourism environment. Research findings about the process of preparing guidebook are compiled based on the community beeds, namely behaviors that need to be developed to participate in the preservation of the coastal tourism environment. The contribution of research is to produce the guidebook for community participation in preserving the coastal tourism environment can become a guideline in the development of coastal tourism.